2017
DOI: 10.1051/0004-6361/201731235
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy evolution in merging clusters: The passive core of the “Train Wreck” cluster of galaxies, A 520

Abstract: Aims. The mergers of galaxy clusters are the most energetic events in the universe after the Big Bang. With the increased availability of multi-object spectroscopy and X-ray data, an ever increasing fraction of local clusters are recognised as exhibiting signs of recent or past merging events on various scales. Our goal is to probe how these mergers affect the evolution and content of their member galaxies. We specifically aim to answer the following questions: Is the quenching of star formation in merging clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 114 publications
3
32
0
Order By: Relevance
“…N AGN /N member , is ∼ 3%. The AGN fraction is similar to the AGN fractions measured in individual clusters (∼ 0.5 − 9%, Deshev et al 2017;Habas et al 2018). However, a direct comparison among the AGN fractions is not trivial because the magnitude limit and spectroscopic completeness of other cluster redshift surveys vary.…”
Section: Agns In A2029supporting
confidence: 82%
“…N AGN /N member , is ∼ 3%. The AGN fraction is similar to the AGN fractions measured in individual clusters (∼ 0.5 − 9%, Deshev et al 2017;Habas et al 2018). However, a direct comparison among the AGN fractions is not trivial because the magnitude limit and spectroscopic completeness of other cluster redshift surveys vary.…”
Section: Agns In A2029supporting
confidence: 82%
“…This hypothesis was denoted the "remnant core" scenario (Markevitch et al 2000), and is appropriate for merging clusters with prominent signatures of recent or ongoing mergers. However, A2142 shows an almost regular morphology and appears relaxed at large radii, unlike 1E 0657-56 (Markevitch et al 2002), A520 (Govoni et al 2001;Markevitch et al 2005;Deshev et al 2017), and other clusters with cold fronts, which clearly appear unrelaxed. Therefore, Tittley & Henriksen (2005); Markevitch & Vikhlinin (2007); Owers et al (2011) proposed an alternative model, where the observed cold fronts derive from a sloshing cool core Chu-razov et al 2003).…”
Section: Introductionmentioning
confidence: 92%
“…Although the lopsided distribution and high amplitudes of radial velocities of our RPS candidates heavily disfavor the specific merger geometry adopted historically for A1758N, the observational evidence nonetheless strongly supports a causal link between RPS and merger events in clusters. Previous studies found two opposing effects of such a link: Stroe et al (2015Stroe et al ( , 2017 and Ruggiero et al (2019) report evidence of RPS triggered by merger-induced shocks, while other studies (Pranger et al 2014;Deshev et al 2017) find the fraction of starforming galaxies in mergers reduced compared to nonmerging clusters, possibly after a preceding short starburst phase. Although seemingly in conflict with each other at face value, these findings might be reconciled as part of a bigger picture in which RPS events in mergers first trigger an initial burst of star formation, and then reduce or completely quench star formation as the supply of atomic and molecular gas is either exhausted or removed from the affected galaxies.…”
Section: The Impact Of Cluster Mergersmentioning
confidence: 98%